ADAPTATION OF SPECIAL JUDO FITNESS TEST FOR KARATE: A STUDY WITH ATHLETES OF BRAZILIAN NATIONAL TEAM. (Fiep Bulletin - online, 2013)
The aim of this study was to propose the adaptation of the Special Judo Fitness Test (SJFT) for the sport of Karate. As specific objectives, we intend to analyze the aerobic performance in various categories of karate, affiliated to Federation Cearense and composing the brazilian national team. The study included four athletes sex male and one female, aged 16 to 20 years and body mass between 48.0 to 65.5 kg. Specific a test was performed with all aerobic endurance athletes, Cooper Test, and the results thereof were compared with the results of SJFT adapted. Comparing the tests there was great similarity in the results of all athletes. It is concluded that the SJFT can be adapted for athletes Karate.
Keywords: Adaptation; Karate and Fitness Assessment